Dinamika Hubungan Dalam Pengolahan Rotan di Buton Utara.abupaten Muna. The Dynamics of the Relationship Among the Societies Based of Rattan Cultivation in The North Buton Region of Muna District. - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTIn the process of cultivation of forestry Rattan production in the North Buton, Muna District, there had involved a largely set of components. In the macro level involved the regional government as the authorities holders for the redistribution of forestry resources. At the other, on the micro level, involved the entrepreneur of the forestry resulting (the entrepreneur of national-scale, entrepreneur of local-scale, the Rattan collectors or brockers)